CT scan screening is associated with increased distress among subjects of the APExS - Stoufflet Audrey; Luc Amandine; Maurel Marion; Paris Christophe; Pairon Jean-Claude; Letourneux Marc (BMC Public Health, 2010)
Abstract Background The aim of this study was to assess the psychological consequences of HRCT scan screening in retired asbestos-exposed workers. Methods A HRCT-scan screening program for asbestos-related diseases was carried out in four regions of France. At baseline (T1), subjects filled in self-administered occupational questionnaires. In two of the regions, subjects also received a validated psychological scale, namely the psychological consequences questionnaire (PCQ). The physician was required to provide the subject with the results of the HRCT scan at a final visit. A second assessment of psychological consequences was performed 6 months after the HRCT-scan examination (T2). PCQ scores were compared quantitatively (t-test, general linear model) and qualitatively (chi²-test, logistic regression) to screening results. Multivariate analyses were adjusted for gender, age, smoking, asbestos exposure and counseling. Results Among the 832 subjects included in this psychological impact study, HRCT-scan screening was associated with a significant increase of the psychological score 6 months after the examination relative to baseline values (8.31 to 10.08, p < 0.0001, t-test). This increase concerned patients with an abnormal HRCT-scan result, regardless of the abnormalities, but also patients with normal HRCT-scans after adjustment for age, gender, smoking status, asbestos exposure and counseling visit. The greatest increase was observed for pleural plaques (+3.60; 95%CI [+2.15;+5.06]), which are benign lesions. Detection of isolated pulmonary nodules was also associated with a less marked but nevertheless significant increase of distress (+1.88; 95%CI [+0.34;+3.42]). However, analyses based on logistic regressions only showed a close to significant increase of the proportion of subjects with abnormal PCQ scores at T2 for patients with asbestosis (OR = 1.92; 95%CI [0.97-3.81]) or with two or more diseases (OR = 2.04; 95%CI [0.95-4.37]). Conclusion This study suggests that HRCT-scan screening may be associated with increased distress in asbestos-exposed subjects. If confirmed, these results may have consequences for HRCT-scan screening recommendations.